Aluminate cement binder light weight amorphous refractory material pulverization behavior inhibiting protective agent and method of making
Patent Information
- Application Number
- CN202611260199.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-19
- Publication Date
- 2026-10-16
AI Technical Summary
在表面防护方面,现有防护剂多针对硅酸盐水泥混凝土材料开发,与铝酸盐水泥水化体系适配性差,存在成膜疏松、耐湿热老化性能不足等问题
[0033] (1) The protective agent described in this invention is highly targeted and has a unique mechanism: it is designed for the hydration system of aluminate cement. The inorganic functional salt can stabilize the crystal form of the hydration products and inhibit the decomposition of the humid heat phase transformation; the dispersed and stable components ensure the long-term storage stability of the liquid; the silicon source components achieve deep penetration and dense film formation on the surface, which is breathable but not water-permeable and does not affect the breathing structure and high-temperature performance of refractory materials, thus completely solving the shortcomings of traditional protective agents such as poor compatibility, easy failure and pore blockage; the formula is simple and does not use corrosive components, making it safer.
Smart Images

Figure CN122916696A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of refractory material performance testing and material protection technology, and in particular relates to an inhibitory protective agent for the pulverization behavior of aluminate cement-bonded lightweight unshaped refractories, its preparation method and application method, and also relates to a rapid evaluation method for the pulverization behavior of aluminate cement-bonded lightweight unshaped refractories. Background Technology
[0002] Lightweight monolithic refractories, due to their low bulk density, low thermal conductivity, and excellent thermal shock resistance, are widely used as working or insulating linings for industrial kilns, power facilities, and petrochemical plants. These materials typically consist of refractory aggregates, fine powder, aluminate cement binders, and admixtures. However, in practical engineering applications, due to construction schedule constraints or extreme weather conditions, the material baking (furnace drying) process often cannot be performed on time or according to standards, resulting in long-term exposure to humid and hot service environments.
[0003] Under these conditions, the hydration products of aluminate cement (CAH10, C2AH8, AH3, etc.) exhibit poor thermodynamic stability and are highly susceptible to crystal transformation, hydrolysis, dissolution, or carbonation decomposition under the combined effects of temperature and humidity. For lightweight systems with high porosity, loose structure, and large binder content, these degradation reactions are more severe, manifesting as surface dusting, whitening, structural loosening, shallow peeling, and even microcrack propagation. Without timely protection, the surface will continue to peel, potentially leading to complete breakage of the green body in severe cases.
[0004] In existing technologies, some solutions address the pulverization problem through optimized formulation or surface treatment. Regarding formulation optimization, CN 120483692A discloses an anti-alkali-rebound aluminate cement-bonded aluminosilicate refractory castable and its preparation method. This method achieves the goal of preventing alkali efflorescence by adding mordenite zeolite, nano-calcium carbonate, and other alkali-inhibiting components to the raw material composition. This method is suitable for manufacturers to optimize formulations from the source. In terms of surface protection, existing protective agents are mostly developed for silicate cement concrete materials, exhibiting poor compatibility with aluminate cement hydration systems and problems such as loose film formation and insufficient resistance to damp heat aging. Patent CN104446655B discloses a reinforcing release agent for inhibiting whitening of amorphous refractory castables and its preparation method. The release agent is prepared using raw materials such as phosphoric acid solution, sulfuric acid solution, and alumina micropowder to prevent alkali metal salts from reacting with carbon dioxide in the air, thereby inhibiting alkali efflorescence. However, the strong acid used in the release agent is corrosive, and the preparation process requires heating and boiling, making it difficult to apply on a large scale. Summary of the Invention
[0005] In view of this, in order to solve the above-mentioned technical problems, the present invention proposes an inhibitory protective agent for pulverization behavior of aluminate cement-bonded lightweight amorphous refractory materials and its preparation method. The protective agent works synergistically from three levels: accelerating hydration, blocking pores, and inhibiting salt migration, so as to effectively inhibit pulverization behavior. Moreover, its formula and preparation process are simple, do not use corrosive components, and are safer.
[0006] To achieve the above objectives, the technical solution of the present invention is implemented as follows:
[0007] The present invention provides an inhibitory protective agent for the pulverization behavior of aluminate cement-bonded lightweight unshaped refractory materials, comprising the following raw material components by mass percentage: 5% to 30% inorganic functional salt, 2% to 10% silicon source component, 0.1% to 0.5% dispersion stabilizing component, and the balance being deionized water, totaling 100%.
[0008] In some preferred embodiments of the aluminate cement-bonded lightweight unshaped refractory powdering inhibition and protection agent of the present invention, the inorganic functional salt is at least one of lithium sulfate, lithium chloride, lithium carbonate, and aluminum dihydrogen phosphate.
[0009] In some preferred embodiments of the aluminate cement-bonded lightweight unshaped refractory powdering inhibition and protection agent of the present invention, the silicon source component is at least one of silica sol solution and organosilicon emulsion.
[0010] In some preferred embodiments of the aluminate cement-bonded lightweight unshaped refractory pulverization inhibition and protection agent of the present invention, the dispersing and stabilizing component is at least one of sodium hexametaphosphate and sodium pyrophosphate.
[0011] The second aspect of the present invention provides a method for preparing a protective agent to inhibit the pulverization behavior of aluminate cement-bonded lightweight amorphous refractory materials, comprising the following steps: adding the dispersion stabilizing component to the deionized water in a proportion and mixing evenly, then adding the inorganic functional salt, and after complete dissolution, slowly adding the silicon source component and mixing evenly to obtain a clear and transparent solution, which is the protective agent.
[0012] In some preferred embodiments of the preparation method of the aluminate cement-bonded lightweight amorphous refractory powdering behavior inhibitor of the present invention, the mixing time after the addition of the dispersing stabilizing component is 1-3 min, the mixing time after the addition of the inorganic functional salt is 10-20 min, and the mixing time after the addition of the silicon source component is 1-4 h; the stirring speed during the mixing process is controlled at 500-1000 r / min.
[0013] The third aspect of the present invention provides a method for using a protective agent to inhibit the pulverization behavior of aluminate cement-bonded lightweight unshaped refractory materials, wherein the protective agent is uniformly covered on the surface of the molded material.
[0014] In some preferred embodiments of the present invention, the protective agent for inhibiting the pulverization behavior of aluminate cement-bonded lightweight unshaped refractory materials is applied to the surface of the molded material by spraying or brushing; the protective agent is applied 1 to 2 times, with an interval of 1 to 4 hours between the two applications, and the dry film thickness formed by a single application is 0.1 to 0.3 mm; the spraying pressure is controlled at 0.2 to 0.4 MPa.
[0015] In some preferred embodiments of the present invention, the protective agent for inhibiting the pulverization behavior of aluminate cement-bonded lightweight unshaped refractory materials is applied to the surface of the molded material by spraying.
[0016] A fourth aspect of this invention provides a rapid evaluation method for the pulverization behavior of aluminate cement-bonded lightweight unshaped refractory materials, comprising the following steps:
[0017] S1. Mix the unshaped refractory material into a mold, smooth the surface, and prepare a sample.
[0018] S2. Apply the protective agent evenly to the surface of the sample; leave the blank sample uncoated.
[0019] S3. Place the sample in a high-temperature and high-humidity accelerated simulation test environment and observe the changes in appearance morphology;
[0020] S4. Determine the powdering grade and wet heat powdering sensitivity of the sample according to the appearance rating standard.
[0021] In some preferred embodiments of the rapid evaluation method for the pulverization behavior of aluminate cement-bonded lightweight unshaped refractory materials of the present invention, in step S1, the size of the sample is (100-300) mm × (100-300) mm × (10-30) mm.
[0022] In S2, the coating method is spraying or brushing, and 1 to 2 coats are applied depending on the sensitivity of the material to chalking, with an interval of 1 to 4 hours between the two coats. The spraying pressure is 0.2 to 0.4 MPa.
[0023] In S3, the conditions of the accelerated simulation test environment with high temperature and high humidity are: temperature 30-50℃, relative humidity 80%-100%, and observation period of 1-7 days.
[0024] In S4, the rating criteria are as follows:
[0025] Level 1 - No Powdering: The overall surface of the sample is intact, without whitening, dusting, or salt precipitation. The surface structure is dense and complete, without defects such as looseness, peeling, or micro-cracks.
[0026] Secondary - Slight Powdering: The sample surface shows only slight whitening and a small amount of floating dust, with no obvious salt precipitation and enrichment. The surface structure is intact, without looseness, peeling, or cracking. The substrate remains dense after wiping.
[0027] Level 3 - Moderate pulverization: Local areas of the sample show obvious whitening and salt accumulation, severe surface dusting, loose local surface layer, powdery feel, and shallow, thin peeling, without penetrating cracks or large-area matrix damage.
[0028] Level IV - Severe Powdering: The sample exhibits large-area whitening and salt precipitation, severe overall dusting, widespread loose powdering of the surface, obvious peeling and flaking in multiple places, accompanied by fine surface cracks, and significant damage to the structural integrity.
[0029] In some preferred embodiments of the rapid evaluation method for the pulverization behavior of aluminate cement-bonded lightweight unshaped refractory materials of the present invention, in step S1, the sample size is 300mm × 150mm × 20mm.
[0030] In some preferred embodiments of the rapid evaluation method for the pulverization behavior of aluminate cement-bonded lightweight unshaped refractory materials of the present invention, in step S2, the coating method is spraying.
[0031] In some preferred embodiments of the rapid evaluation method for the pulverization behavior of aluminate cement-bonded lightweight unshaped refractory materials of the present invention, in step S3, the conditions of the accelerated simulation test environment with high temperature and high humidity are 40-50°C, 90%-95% relative humidity, and an observation period of 3 days.
[0032] Compared with existing technologies, the aluminate cement-bonded lightweight unshaped refractory pulverization inhibition and protection agent, its preparation method, application method, and evaluation method described in this invention have the following advantages:
[0033] (1) The protective agent described in this invention is highly targeted and has a unique mechanism: it is designed for the hydration system of aluminate cement. The inorganic functional salt can stabilize the crystal form of the hydration products and inhibit the decomposition of the humid heat phase transformation; the dispersed and stable components ensure the long-term storage stability of the liquid; the silicon source components achieve deep penetration and dense film formation on the surface, which is breathable but not water-permeable and does not affect the breathing structure and high-temperature performance of refractory materials, thus completely solving the shortcomings of traditional protective agents such as poor compatibility, easy failure and pore blockage; the formula is simple and does not use corrosive components, making it safer.
[0034] (2) The preparation method of the protective agent described in this invention is simple and mild, highly operable, and conducive to large-scale production and application.
[0035] (3) The evaluation method described in this invention is accurate, efficient and fits engineering. By setting up an accelerated simulation test environment with high temperature and high humidity, the detection cycle is shortened to within 7 days. The evaluation is based on the intuitive defects in appearance and morphology, and matches the service assessment standards of refractory materials. The evaluation results have good repeatability and high accuracy.
[0036] (4) The lightweight unshaped refractory material treated with the protective agent described in this invention, after being verified by the high temperature and high humidity accelerated evaluation described in this invention, has no powdering defects such as dusting, loosening, peeling, and cracking on the surface, and can resist the erosion of humid and hot environment for a long time, greatly improving the service life of the material. Attached Figure Description
[0037] Figure 1 These are photographs of actual samples used in the pulverization performance test as described in Embodiment 1 of the present invention. In Figure A, the sample is without protective agent coating, and in Figure B, the sample is with protective agent coating.
[0038] Figure 2 These are photographs of actual samples used in the pulverization performance test as described in Embodiment 2 of the present invention. In Figure A, the sample is uncoated with protective agent, and in Figure B, the sample is coated with protective agent.
[0039] Figure 3 These are photographs of actual samples used in the pulverization performance test as described in Embodiment 3 of the present invention. In Figure A, the sample is uncoated with protective agent, and in Figure B, the sample is coated with protective agent. Detailed Implementation
[0040] Unless otherwise defined, the technical terms used in the following embodiments have the same meanings as commonly understood by those skilled in the art. Unless otherwise specified, the experimental reagents used in the following embodiments are conventional biochemical reagents; and the experimental methods described are conventional methods.
[0041] The present invention will be described in detail below with reference to the embodiments.
[0042] Example 1
[0043] Preparation of protective agent: Weigh 3 wt% lithium chloride, 10 wt% aluminum dihydrogen phosphate, 5 wt% silica sol, and 0.2 wt% sodium hexametaphosphate, with the remainder being deionized water; add sodium hexametaphosphate to deionized water and stir evenly, then add lithium chloride and stir for 10 min, then slowly add aluminum dihydrogen phosphate solution dropwise and stir until clear and transparent, then add silica sol and stir for 1.5 h at a stirring speed of 600 r / min to obtain a clear and transparent solution, which is the protective agent.
[0044] Powdering performance test: A conventional aluminate cement-bonded lightweight insulating castable was selected and mixed evenly with water. Using a cement board as a base, a pre-painted molding mold (300×150×20 mm) was placed inside. The mixed lightweight material was then placed into the mold and tamped evenly with a tamping rod. The surface was then smoothed and leveled with a trowel, ensuring the trowel surface was dry to avoid affecting the appearance. The molding frame was gently removed to obtain the specimen sample. Two parallel tests were conducted: the first set of specimens was placed in a test chamber at 50℃ and 90% humidity immediately after preparation; the second set was placed in a test chamber under the same conditions after being coated with the prepared protective agent. The specimens were observed after 3 days of curing. The surface morphology is as follows. Figure 1 As shown, the uncoated sample surface was severely powdery and peeled off over a large area, earning a rating of Level 4; the sample coated with protective agent had a relatively intact surface with no obvious defects, earning a rating of Level 1.
[0045] Example 2
[0046] Preparation of protective agent: Weigh 10wt% lithium sulfate, 5wt% aluminum dihydrogen phosphate, 5wt% organosilicon emulsion, and 0.5wt% sodium pyrophosphate, with the remainder being deionized water; add sodium pyrophosphate to deionized water and stir evenly, then add lithium sulfate and stir for 10 min, then slowly add aluminum dihydrogen phosphate solution dropwise and stir until clear and transparent, then add organosilicon emulsion and stir for 3 h at a stirring speed of 650 r / min to obtain a clear and transparent solution, which is the protective agent.
[0047] Powdering performance test: Conventional aluminate cement combined with lightweight scraper coating was selected and mixed evenly with water. Using a cement board as a base, a pre-painted molding mold (300×150×20 mm) was placed inside. The mixed lightweight material was then placed into the mold and tamped evenly with a tamping rod. The mold was then smoothed and leveled with a trowel, ensuring the trowel surface was dry to avoid affecting the appearance. The molding frame was gently removed to obtain the specimen sample. Two parallel tests were conducted: the first set of specimens was placed in a test chamber at 40℃ and 95% humidity immediately after preparation; the second set was placed in a test chamber under the same conditions after being sprayed with the prepared protective agent. The specimens were observed after 3 days of curing. The surface morphology is as follows. Figure 2 As shown. The uncoated sample had severe mold growth, chalking, and lack of surface strength, and was rated as Level 4; the sample coated with protective agent had a complete surface with no obvious defects, and was rated as Level 1.
[0048] Example 3
[0049] Preparation of protective agent: Weigh 2wt% lithium chloride, 2wt% lithium carbonate, 3wt% aluminum dihydrogen phosphate, 10wt% silica sol solution, 0.5wt% sodium pyrophosphate, and the remainder is deionized water; add sodium pyrophosphate to water and stir evenly, then add lithium chloride and lithium carbonate, stir for 15 min, then slowly add aluminum dihydrogen phosphate solution dropwise, stir until clear and transparent, then add silica sol solution, stir for 2 h at a stirring speed of 600 r / min, and the clear and transparent solution obtained is the protective agent.
[0050] Powdering performance test: Conventional aluminate cement combined with lightweight scraper coating was selected and mixed evenly with water. Using a cement board as a base, a pre-painted molding mold (300×150×20 mm) was placed inside. The mixed lightweight material was then placed into the mold and tamped evenly with a tamping rod. The mold was then smoothed and leveled with a trowel, ensuring the trowel surface was dry to avoid affecting the appearance. The molding frame was gently removed to obtain the specimen sample. Two parallel tests were conducted: the first set of specimens was placed in a test chamber at 40℃ and 80% humidity immediately after preparation; the second set was placed in a test chamber under the same conditions immediately after molding and spraying with the prepared protective agent. The specimens were observed after 3 days of curing. The surface morphology is as follows. Figure 3 As shown, the uncoated sample had severe peeling and flaking, and was rated as Level 4; the sample coated with protective agent had a complete surface with no obvious defects, and was rated as Level 1.
[0051] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A protective agent for inhibiting the pulverization behavior of aluminate cement-bonded lightweight unshaped refractory materials, characterized in that, It includes the following raw material components by mass percentage: 5%–30% inorganic functional salts, 2%–10% silicon source components, 0.1%–0.5% dispersion stabilizing components, and the balance being deionized water, totaling 100%.
2. The aluminate cement-bonded lightweight unshaped refractory material pulverization inhibitor and protective agent according to claim 1, characterized in that: The inorganic functional salt is at least one of lithium sulfate, lithium chloride, lithium carbonate, and aluminum dihydrogen phosphate.
3. The aluminate cement-bonded lightweight unshaped refractory material pulverization inhibitor and protective agent according to claim 1, characterized in that: The silicon source component is at least one of silica sol solution and organosilicon emulsion.
4. The aluminate cement-bonded lightweight unshaped refractory material pulverization inhibitor and protective agent according to claim 1, characterized in that: The dispersing and stabilizing component is at least one of sodium hexametaphosphate and sodium pyrophosphate.
5. The method for preparing the pulverization inhibition and protective agent for aluminate cement-bonded lightweight unshaped refractory materials according to any one of claims 1 to 4, characterized in that, The process includes the following steps: adding the dispersible stabilizing component to the deionized water in a certain proportion and mixing evenly, then adding the inorganic functional salt, and after it is completely dissolved, slowly adding the silicon source component and mixing evenly to obtain a clear and transparent solution, which is the protective agent.
6. The preparation method of the aluminate cement-bonded lightweight unshaped refractory pulverization inhibition and protective agent according to claim 5, characterized in that: The mixing time after adding the dispersing and stabilizing component is 1-3 min, the mixing time after adding the inorganic functional salt is 10-20 min, and the mixing time after adding the silicon source component is 1-4 h; the stirring speed during the mixing process is controlled at 500-1000 r / min.
7. The method of using the aluminate cement-bonded lightweight unshaped refractory pulverization inhibition and protective agent according to any one of claims 1 to 4, characterized in that: The protective agent is evenly applied to the surface of the molded material.
8. The method of using the aluminate cement-bonded lightweight unshaped refractory material pulverization inhibition and protection agent according to claim 7, characterized in that: The protective agent is applied to the surface of the molded material by spraying or brushing; the protective agent is applied 1 to 2 times, with an interval of 1 to 4 hours between the two applications, and the dry film thickness formed by a single application is 0.1 to 0.3 mm; the spraying pressure is controlled at 0.2 to 0.4 MPa.
9. A rapid evaluation method for the pulverization behavior of aluminate cement-bonded lightweight unshaped refractory materials, characterized in that, Includes the following steps: S1. Mix the unshaped refractory material into a mold, smooth the surface, and prepare a sample. S2. Apply the protective agent evenly to the surface of the sample; leave the blank sample uncoated. S3. Place the sample in a high-temperature and high-humidity accelerated simulation test environment and observe the changes in appearance morphology; S4. Determine the powdering grade and wet heat powdering sensitivity of the sample according to the appearance rating standard.
10. The rapid evaluation method for the pulverization behavior of aluminate cement-bonded lightweight unshaped refractory materials according to claim 9, characterized in that: In S1, the size of the sample is (100~300) mm × (100~300) mm × (10~30) mm; In S2, the coating method is spraying or brushing, and 1 to 2 coats are applied depending on the sensitivity of the material to chalking, with an interval of 1 to 4 hours between the two coats. The spraying pressure is 0.2 to 0.4 MPa. In S3, the conditions of the accelerated simulation test environment with high temperature and high humidity are: temperature 30-50℃, relative humidity 80%-100%, and observation period of 1-7 days. In S4, the rating criteria are as follows: Level 1 - No Powdering: The overall surface of the sample is intact, without whitening, dusting, or salt precipitation. The surface structure is dense and complete, without defects such as looseness, peeling, or micro-cracks. Secondary - Slight Powdering: The sample surface shows only slight whitening and a small amount of floating dust, with no obvious salt precipitation and enrichment. The surface structure is intact, without looseness, peeling, or cracking. The substrate remains dense after wiping. Level 3 - Moderate pulverization: Local areas of the sample show obvious whitening and salt accumulation, severe surface dusting, loose local surface layer, powdery feel, and shallow, thin peeling, without penetrating cracks or large-area matrix damage. Level IV - Severe Powdering: The sample exhibits large-area whitening and salt precipitation, severe overall dusting, widespread loose powdering of the surface, obvious peeling and flaking in multiple places, accompanied by fine surface cracks, and significant damage to the structural integrity.
Citation Information
Patent Citations
Reinforcing release agent for inhibiting unshaped refractory castable from returning to white hair and preparation method thereof
CN104446655B